Taxonomy of the leafhopper genus Nirvanguina (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with description of a new species from China - Xu, Deliang; Li, Shuying; Zhang, Yalin (Zootaxa, 2021)
The leafhopper genus Nirvanguina Zhang & Webb (Cicadellidae: Deltocephalinae: Drabescini: Paraboloponina) is reviewed, including description of a new species, Nirvanguina bifurcatus Xu & Zhang sp. nov., from China. An updated checklist along with distribution and a key to males of this genus are also provided. Type specimens of this new species are deposited in the Entomological Museum, Northwest A&F University, Yangling, Shaanxi, China (NWAFU).